1995
DOI: 10.1007/bf00204858
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic imaging of the hand and wrist in rheumatoid arthritis

Abstract: Ultrasound can detect abnormalities of the hand and wrist in patients with rheumatoid arthritis compared to normal volunteers. Normal articular anatomy is well demonstrated ultrasonically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…The selected papers were then divided among the group members and assessed according to an agreed scoring sheet (for results of Evaluation score, see Table 1) 4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Resultsmentioning
confidence: 99%
“…The selected papers were then divided among the group members and assessed according to an agreed scoring sheet (for results of Evaluation score, see Table 1) 4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Resultsmentioning
confidence: 99%
“…An erosion was defined as a break in the cortex visible in both transverse and longitudinal planes measuring 2 mm or more [24]. A graded scale was used in which an absence of erosions scored 0, 1-2 erosions scored 1, more than two erosions scored 2 and any large erosions (areas of regional bone destruction) scored 3 [24].…”
Section: Us Scoresmentioning
confidence: 99%
“…of synovial thickness (with high-frequency 20-MHz transducers) and vascularization (power Doppler US), and early detection of erosions (87)(88)(89). A metaanalysis of 21 studies including 913 patients with RA showed that US was more effective than radiography in the detection of erosions (odds ratio, 0.30; P , .00001), and its efficacy was comparable to that of MR imaging (90).…”
Section: Sodium Imagingmentioning
confidence: 99%